In Vivo Bioequivalence Study of Drug: An Analysis of Bidding in Vietnam Period 2018 - 2022 - Quoc Hung, Tang; Thanh Hai, Nguyen; Bich Ngoc, Tran; Thi Thu Thu, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2024)
To promote the development of bioequivalent drugs, the Ministry of Health of Vietnam has classified a separate bidding group for bioequivalent drugs. According to the results of bidding for bioequivalent drugs in the period 2018 - 2022 has achieved very encouraging results, the ratio of domestic bioequivalent drugs compared to foreign bioequivalent drugs winning bids is from 2.13 to 3.63 times higher. Regarding active pharmaceutical ingredients of bioequivalent drugs, bioequivalent drugs with the highest total winning value (including all dosage forms, concentrations,...) focus mainly on antibiotics (cefuroxime, cefixime,…), anti-diabetic drugs (gliclazide, metformin,...), high blood pressure drugs (amlodipine), antipyretic and pain relievers (paracetamol). The winning drug dosage forms are still mainly conventional dosage forms (tablets, film-coated tablets, capsules) and their active ingredients are almost single. In particular, several multi-component bioequivalence drugs have a large total winning value but do not belong to the pharmaceutical group on the list of mandatory bioequivalence test reports when registering the drug, such as the combination of Gliclazide + Metformin; Glibenclamide + Metformin; Glimepiride + Metformin. The trend of selecting pharmaceutical substances/groups of pharmaceutical substances that manufacturers focus on researching/registering bioequivalent drugs in Vietnam is focused on drugs on the list of drugs covered by health insurance.